Polish oncology in Internet - Kopacz, Andrzej; Drucis, Kamil; Jastrzębski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2002)
The article presents review of polish oncology in the Internet. It presents the websites created by departments, pharmaceutical companies, research institutes, doctors and also private websites. Authors publish the URL addresses, where articles concerning oncology can be found, links to other medical websites, on-line atlases. In the article there is a description of the most interesting websites as well. Websites are addressed not only to doctors, but also, and to patients looking for information and their families. Groups of patients helping one another in the Internet are also of great weight. Although the Internet is used by more than 700.000 mostly young people the majority of them does not trust data downloaded from the web. The highest percentage of satisfied users is among doctors. Apart from providing information internet enables the development of telemedicine. An excellent example is telepathology diagnose of neuropathology cases in Poznan. Internet in Polish provides not as many pieces of information as it's English version, but it's closer polish realities - referring to treatment and life. It enables also getting into touch with a doctor close to permanent residence. Internet is still not the main source of data comparing with books or TV. It can not replace diagnosis or the medical examination of the patient. Internet however educates the patient what a neoplasm is, how it can be treated, and forces doctors to improve their knowledge constantly.